Impact of academic self-efficacy on entrepreneurial intention of Portuguese higher education students - Ribeiro, Maria Isabel (2020)
Self-efficacy has a significant and positive impact on entrepreneurial intention [1] and, in an academic context, self-efficacy has a positive effect on motivation and student’s performance [2]. So, this research aimed to verify if academic self-efficacy of higher education students is a predictor of their intention to create new businesses. To achieve this objective, a quantitative and cross-sectional study was carried out based on a probabilistic sample of 1329 Portuguese students who attended, in 2018-2019 academic year, a higher education institution located in Northeast Portugal. To collect the data, a questionnaire was administered to the students, in the classroom, from October 2018 until January 2019. The anonymity and data confidentiality were guaranteed to all students and their participation was voluntary. The questionnaire was organized in three sections. The first section included academic and sociodemographic variables. The second section included the academic self-efficacy scale validated for Portugal [3]. This scale includes ten items evaluated in a Likert scale ranging from 1 (strongly disagree) to 7 (strongly agree). Finally, the third section comprised the entrepreneurial scale [4] that includes four items evaluated in a Likert scale ranging from 1 (a little) to 7 (a lot). Students were aged between 17 and 47 years old and attended a degree course within four different scientific areas, namely Education (62.1%), Technologies and Management (21.1%), Health (10.8%) and Agriculture (5.9%). The majority was female (54.7%) and attended a 1st cycle degree course (88.3%) in an ordinary full-time attendance mode (96.5%). Most students registered a high level of academic self-efficacy (47.3%) and a low level of entrepreneurial intention (39.5%). Academic selfefficacy presents a significant (sig. = 0.000), positive and moderate correlation (Pearson’s R = 0.573) with entrepreneurial intention. A significant linear regression model was estimated (sig. = 0.000) showing that academic self-efficacy is a predictor that explains 32.9% of entrepreneurial intention variance. These results provide empirical evidence that academic self-efficacy has a statistically significant and positive impact on entrepreneurial intention. So, the institution must focus on the development of students’ academic performance in order to increase their intention to create new businesses